PENGARUH PENGGUNAAN MEDIA STORYBOARD FILL-IN-THE-BLANK BERBASIS EDUCATIONAL MOBILE GAME TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN CERITA SISWA KELAS IV SD INPRES MALLENGKERI BERTINGKAT - Muakipa; Karumpa, Aco; Zulfika, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using fill-in-the-blank storyboard media based on educational mobile games on the reading comprehension skills of fourth-grade students at SD Inpres Mallengkeri Bertingkat. The type of research used is a pre-experimental design with a one-group pretest-posttest design, namely an experiment involving one class without a comparison class. The population in this study were all fourth-grade students at SD Inpres Mallengkeri Bertingkat, totaling 26 students and also used as research samples. Data collection techniques used include observation, tests, and documentation. The data obtained were then analyzed using descriptive and inferential statistical analysis. The results showed that the use of fill-in-the-blank storyboard media based on educational mobile games had an effect on students' reading comprehension skills. This was seen from the increase in student learning outcomes between pretest and posttest scores. Before being given treatment, students' reading comprehension skills were still relatively low and most students had not reached the minimum completion criteria (KKM). However, after the application of fill-in-the-blank storyboard media based on educational mobile games, student learning outcomes increased significantly and all students had achieved learning completion. Based on the results of the hypothesis test using a paired sample t-test, a significance value (Sig. 2-tailed) of 0.000 < 0.05 was obtained, thus H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that the use of fill-in-the-blank storyboard media based on educational mobile games significantly influenced the reading comprehension skills of fourth-grade students at SD Inpres Mallengkeri Bertingkat.